Impact of intellectual capital on innovation capability and organizational performance: An empirical investigation - Barkat, Waseem; Beh, Loo See; Ahmed, Adeel; Ahmed, Riaz (University of Belgrade, 2018)
Intellectual capital has much contribution for organizational value creation in developed nations, but it is still in progressing stages in developing countries. This study aims to develop a model to investigate the effects of different dimensions of intellectual capital on innovation capability and organizational performance. Data were collected from 295 respondents in large textile companies in Pakistan. This study found significant positive direct and indirect effects on innovation capability and organizational performance among three dimensions of intellectual capital: human, relational, and technological. This research presents the implications for HR managers and policy makers in incorporating intellectual capital. This study contributes to bridge the gap in research by examining the effects of different dimensions of intellectual capital on organizational performance in the context of a developing country.